2017
DOI: 10.1021/acs.nanolett.7b03789
|View full text |Cite
|
Sign up to set email alerts
|

High-Mobility, Ultrathin Organic Semiconducting Films Realized by Surface-Mediated Crystallization

Abstract: The functionality of common organic semiconductor materials is determined by their chemical structure and crystal modification. While the former can be fine-tuned via synthesis, a priori control over the crystal structure has remained elusive. We show that the surface tension is the main driver for the plate-like crystallization of a novel small organic molecule n-type semiconductor at the liquid-air interface. This interface provides an ideal environment for the growth of millimeter-sized semiconductor platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 21 publications
2
84
0
Order By: Relevance
“…Zhang et al observed a better molecular packaging in the poly(diketopyrrolopyrrole‐thiophene‐thieno[3,2,b]thiophene‐thiophene) (DPP2T‐TTT) thin film when the system surface energy decreased . Similar results of surface energy regulation have been perceived by Vladimirov et al They observed n‐type crystals could start to grow at the solvent–air interface if the surface energy of solvents was higher than that of crystals . Other than the experimental parameters, physical modeling has also been employed to investigate the crystallization process of the thin films.…”
Section: Introductionmentioning
confidence: 71%
“…Zhang et al observed a better molecular packaging in the poly(diketopyrrolopyrrole‐thiophene‐thieno[3,2,b]thiophene‐thiophene) (DPP2T‐TTT) thin film when the system surface energy decreased . Similar results of surface energy regulation have been perceived by Vladimirov et al They observed n‐type crystals could start to grow at the solvent–air interface if the surface energy of solvents was higher than that of crystals . Other than the experimental parameters, physical modeling has also been employed to investigate the crystallization process of the thin films.…”
Section: Introductionmentioning
confidence: 71%
“…Although chirality is textbook concept in synthetic chemistry, few chiral organic semiconductors have been reported so far, in contrast of chiral conjugated polymers and chiral organic conductors that have received more attention . There are essentially two types of molecular structures, either the π‐systems are chiral and depart from planarity or chiral side‐groups are attached to a flat conjugated core . Figure presents a selection of some chiral semiconductors.…”
Section: Charge Transportmentioning
confidence: 99%
“…Guiding Monolayer Formation with Uniform Microstructures : Driven by the attractive properties of 2D materials such as planar surface, ultrahigh carrier mobility, and sensitivity, considerable attention has been focused on the organic monolayer and few‐layer transistors for novel multifunctional optoelectronics, However, it is not facile to fabricate a few‐layer structure for organic materials because of weak π–π interactions. The resulting films often consist of polycrystalline phases rather than continuous single‐crystalline phases …”
Section: Optimization Of Nonideal Ofetsmentioning
confidence: 99%